Statement by the Managing Director on the FY 2023 Work Program of the Executive Board : Executive Board Meeting - June 8, 2022. (Policy Papers; Policy Paper ;, 2022)
The Work Program aims to help the membership tackle multiple and complex challenges-most prominently high inflation, along with elevated debt levels, energy and food security, and risks of fragmentation. In addition to discussing policy advice, financial assistance, and capacity development to provide critical support to the countries affected by these compounding crises, the Board will continue to monitor closely the economic and financial developments, new challenges and risks, and discuss policy responses. Work will also focus on implementing the strategies to support a more resilient, inclusive, digital, and green global economy.